Injection molding of micro-porous Ti10Nb10Zr alloy - (:unkn) unknown (Metal Powder Industries Federation, 2017)
The powder space holder (PSH) and powder injection molding (PIM) methods have a biomaterial industrial competitive advantage that is capable of net-shape production of the micro-sized porous parts. In this study, micro-porous Ti10Nb10Zr alloys were produced by PSH-PIM process. Ti10Nb10Zr alloy powder and spherical polymethylmethacrylate (PMMA) particles were used as a space holder material. After molding, binder debinding was performed by thermal method under inert gas. Debinded samples were sintered at 1300ºC for 60 min in a vacuum. Metallographic studies were conducted to determine densification and the corresponding microstructural changes. The surface of sintered samples was examined by SEM. The density and compressive stress of the micro-porous Ti10Nb10Zr samples were determined. The effects of fraction of PMMA on the properties of sintered micro-porous Ti10Nb10Zr samples were investigated. It was shown that the fraction of PMMA could be controlled to affect the properties of the Ti10Nb10Zr alloy. © 2017 Metal Powder Industries Federation. All Rights Reserved.